2010
DOI: 10.1152/ajpgi.00435.2009
|View full text |Cite
|
Sign up to set email alerts
|

Molecular determinants dictating cell surface expression of the human sodium-dependent vitamin C transporter-2 in human liver cells

Abstract: The human sodium-dependent vitamin C transporter-2 (hSVCT2) plays an important role in cellular accumulation of ascorbic acid in liver cells. However, little is known about the molecular determinants that direct hSVCT2 to the cell surface in hepatocytes. We addressed this issue using live cell imaging methods to resolve the distribution and trafficking of truncated or mutated hSVCT2 constructs in a cellular model of human hepatocytes, HepG2 cells. Whereas a full-length hSVCT2-yellow fluorescent protein (YFP) f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 41 publications
1
9
0
Order By: Relevance
“…Many nutrient/substrate transporters contain sequences/regions that are important for their function and targeting to cell membrane that are embedded within their N-terminal [ 24 , 31 ], C-terminal [ 23 , 24 , 32 , 33 ], and/or transmembrane backbone [ 34 , 35 ]. In this study, we show that both the N- (amino acids 1–9) and the C- terminal (amino acids 425–445) sequences of the hRFVT-2 protein are important for its function and cell biology.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many nutrient/substrate transporters contain sequences/regions that are important for their function and targeting to cell membrane that are embedded within their N-terminal [ 24 , 31 ], C-terminal [ 23 , 24 , 32 , 33 ], and/or transmembrane backbone [ 34 , 35 ]. In this study, we show that both the N- (amino acids 1–9) and the C- terminal (amino acids 425–445) sequences of the hRFVT-2 protein are important for its function and cell biology.…”
Section: Discussionmentioning
confidence: 99%
“…After 24–48 hrs transient transfection cells were used for imaging. For stable transfection, U87 cells were selected using G418 (0.5 mg/ml) (Invitrogen) for 4–6 weeks as described before [ 23 , 24 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Myosin II was found to be enriched in the actin microfilament network around the bile canaliculus and was identified as the essential motor for the bile canalicular contraction [25] [27] . Moreover, myosin II is involved in vesicle trafficking between the cytoplasmic compartment and plasma membrane and regulates the apical membrane expression of several transporters associated with bile secretion, such as the bile salt export pump, whose genetic defects are associated with some forms of familiar intrahepatic cholestasis [28] , [29] . Recent studies identified additional key roles for myosin II in hepatocytes, since it was implicated in postnatal hepatocytes polyploidization [30] spatial reorganization of hepatocytes during development and liver regeneration [31] , and cell cycle progression and motility [32] , [33] .…”
Section: Discussionmentioning
confidence: 99%
“…The localization of SVCT2 within the cell may determine its transport activity, although data are conflicting. SVCT2 protein can be retained within intracellular compartments or transport vesicles and may have different kinetic properties depending on its localization ( 63 ), but data in cancer cells are limited. In neurons in culture, SVCT2 translocated to the plasma membrane upon increased extracellular ascorbate concentration ( 64 ).…”
Section: Sodium-dependent Vitamin C Transportermentioning
confidence: 99%